Feminine gender expression and gender nonconformity in Scott Stuart's My Shadow is Pink: a queer reading - Nadia Riskia Safitri (Centre for Literary and Cultural Studies, 2026)
This study examines the representation of feminine gender expression and gender nonconformity in Scott Stuart’s illustrated children’s book My Shadow is Pink (2020). Situated within discussions of gender diversity in children’s literature, the study explores how non-normative gender expression is constructed and negotiated in a heteronormative context. Using a qualitative multimodal approach, this research analyses the interaction between verbal narration and visual elements, including colour, clothing, and gender-coded objects. Drawing on Kress and van Leeuwen’s (2006) multimodal framework, the study examines representational and compositional meanings, while Judith Butler’s concept of gender performativity and Sally Hines’s perspective on gender expression and social response guide the analytical process.The findings reveal three main forms of feminine gender expression: symbolic imagery, clothing, and gender-coded objects. These elements not only reflect the child’s internal struggle but also illustrate how gender identity is performed and negotiated through everyday practices. In addition, the study highlights the significant role of familial response, particularly the father’s evolving attitude, in shaping the child’s emotional experience and process of self-acceptance. Overall, My Shadow is Pink offers a nuanced portrayal of gender nonconformity in childhood and underscores the importance of supportive social environments in enabling children to express their identities.